Genomic epidemiological analysis identifies high relapse among individuals with recurring tuberculosis and provides evidence of recent household-related transmission of tuberculosis in Ghana. (May 2021) - Asare, Prince; Osei-Wusu, Stephen; Baddoo, Nyonuku Akosua; Bedeley, Edmund; Otchere, Isaac Darko; Brites, Daniela; Loiseau, Chloé; Asante-Poku, Adwoa; Prah, Diana Ahu; Borrell, Sonia; Reinhard, Miriam; Omari, Michael Amo; et al.
Highlights: Unresolved previous infection as major cause of recurring tuberculosis (TB) in Ghana. Genomic epidemiology identifies high relapse among recurrent TB cases in Ghana. 15-locus MIRU-VNTR typing is sufficient to predict the cause of TB recurrence. Evidence of recent household-related TB transmission in Ghana. Need for increased education by national TB control program. Abstract: Objective: To retrospectively investigate the cause of recurring tuberculosis ( rc TB) among participants with pulmonary TB recruited from a prospective population-based study conducted between July 2012 and December 2015. Methods: Mycobacterium tuberculosis complex isolates obtained from rc TB cases were characterized by standard mycobacterial genotyping tools, whole-genome sequencing, and phylogenetic analysis carried out to assess strain relatedness. Results: The majority (58.3%, 21/36) of study participants with rc TB episodes had TB recurrence within 12 months post treatment. TB strains with isoniazid (INH) resistance were found in 19.4% (7/36) of participants at the primary episode, of which 29% (2/7) were also rifampicin-resistant. On TB recurrence, an INH-resistant strain was found in a larger proportion of participants, 27.8% (10/36), of which 40% (4/10) were MDR-TB strains. rc TB was attributed to relapse (same strain) in 75.0% (27/36) of participants and 25.0% (9/36) to re-infection. Conclusion: Our findings indicate that previous unresolved infectiondue to inadequate treatment, may be the major cause of rc TB.